2010
DOI: 10.1111/j.1360-0443.2010.02905.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone maintenance therapy promotes initiation of antiretroviral therapy among injection drug users

Abstract: Aims Despite proven benefits of antiretroviral therapy (ART), many HIV-infected injection drug users (IDU) do not access treatment even in settings with free health care. We examined whether methadone maintenance therapy (MMT) increased initiation and adherence to ART among an IDU population with free health care. Design We prospectively examined a cohort of opioid-using antiretroviral-naïve HIV-infected IDU and investigated factors associated with initiation of antiretroviral therapy as well as subsequent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 41 publications
7
110
1
1
Order By: Relevance
“…This is consistent with previous studies that found adherence to ART was typically lower among younger individuals 35 and those in the sex trade 36 while engagement in MMT was associated with better adherence. 37 Interestingly, although the strength of the effect of recent incarceration in a prison or penitentiary also declined, it remained significantly associated with rebound. This highlights the critical need to improve adherence in criminal justice settings.…”
Section: Discussionmentioning
confidence: 98%
“…This is consistent with previous studies that found adherence to ART was typically lower among younger individuals 35 and those in the sex trade 36 while engagement in MMT was associated with better adherence. 37 Interestingly, although the strength of the effect of recent incarceration in a prison or penitentiary also declined, it remained significantly associated with rebound. This highlights the critical need to improve adherence in criminal justice settings.…”
Section: Discussionmentioning
confidence: 98%
“…The initiation of substitution therapy can also increase the uptake of other medications including cART [84 ]. Daily dispensing programs that provide methadone and cART at the same location increase adherence to both therapies and allow closer monitoring and support [85].…”
Section: Treatment Of Hiv Infection In Idus With Hiv/hcvmentioning
confidence: 99%
“…The lower uptake of ART and the poorer outcomes observed among HIV+ people who inject illicit drugs are thought to be attributable to a variety of factors, such as delays in starting treatment, poor adherence to ART, continuing drug dependence and a high prevalence of comorbidities, such as depression and hepatitis C. 19 Internationally, there is growing evidence that treatment of opioid dependence, such as methadone maintenance treatment (MMT), not only stabilizes drug dependence and its associated psychosocial conditions, but also promotes adherence to ART and improves virological responses among HIV+ people. 18,[20][21][22][23] Although China's national ART and MMT programmes have been shown to benefit their respective target populations when assessed independently, 6,[9][10][11]24,25 the advantages of coincident ART and MMT for HIV+ people who inject opioids have not yet been examined in China, though they have Objective To examine the effect of methadone maintenance treatment (MMT) on mortality in people injecting opioids who receive antiretroviral therapy (ART) for the treatment of human immunodeficiency virus (HIV) infection in China. Methods The study involved a nationwide cohort of 23 813 HIV-positive (HIV+) people injecting opioids who received ART between 31 December 2002 and 31 December 2011.…”
Section: Introductionmentioning
confidence: 99%
“…been observed in other settings. 13,20,23,26,27 The aim of this study, therefore, was to determine whether MMT reduces mortality in HIV+ people who inject opioids and are receiving ART through China's national ART programme.…”
Section: Introductionmentioning
confidence: 99%